STRUKTUR KOMUNITAS KARANG DI PERAIRAN PULAU PASUMPAHAN - Purnama, Arief Anthonius (Universitas Pasir Pengaraian, 2013)
Research about Community Sructure of Coral in Pasumpahan Island had been conducted from October 2008 to January 2009. This study are to know composition and community structure of coral in Pasumpahan Island. Stratified systematic sampling method used from two areas (west-south and earth-north) and two the deepness (3-5 m and 7-10 m). There are 45 coral species belong to 12 family. The highest relative densitity of coral species (42.63 %) was found Porites nigrescens, followed by P. lobata (15.8 %), Goniastrea aspera (9,71 %), Poriteslutea (9.46 %), and Favia sp 1 (4.08 %). Diversity index of coral was 1.91 up 0.78 to 2.02. The composition of corals both of the two areas and two deepness were not similar and staying in condition depress-labile, index of similarity range from20.51-42.42 and index of equitability 0.38-0.34.